Obesitas pada Anak - Norberta, Jesslyn (PT Kalbe Farma Tbk., 2024)
The global prevalence of obesity in children increases every year. Many factors influence the occurrence of obesity in children. Diagnosis is based on the distribution of fatty tissue with typical clinical manifestations such as a rounded face, chubby cheeks, double chin, relatively short neck, pendulous abdomen, and abdominal striae. Management and prevention are essential to prevent metabolic syndrome in children.